Astrocyte Heterogeneity in Multiple Sclerosis: Current Understanding and Technical Challenges - Lo, Chih Hung; Skarica, Mario; Mansoor, Mohammad; Bhandarkar, Shaan; Toro, Steven; Pitt, David (Frontiers in Cellular Neuroscience, 2021)
The emergence of single cell technologies provides the opportunity to characterize complex immune/central nervous system (CNS) cell assemblies in multiple sclerosis (MS) and to study their cell population structures, network activation and dynamics at unprecedented depths. In this review, we summarize the current knowledge of astrocyte subpopulations in MS tissue and discuss the challenges associated with resolving astrocyte heterogeneity with single-nucleus RNA-sequencing (snRNA-seq). We discuss multiplexed imaging techniques as tools for defining population clusters within a spatial context. Finally, we will provide an outlook on how these technologies may aid in answering unresolved questions in MS, such as the glial phenotypes that drive MS progression and/or neuropathological differences between different clinical MS subtypes.